The Reliability and Factorial Validity of the Swedish Version of the Revised Controlling Behaviors Scale. Issue 18 (September 2019) - Jansson, Billy; Sundin, Örjan
This study focused on the factor structure of the victimization form of the revised Controlling Behaviors Scale (CBS-R). Data from 1, 218 women and men were analyzed in the study. Results of confirmatory factor analysis (CFA) failed to find support for the proposed five-factor structure of the scale, as the items on the scale were better represented by one common factor. In addition, when examining if controlling behaviors are distinct from psychological aggression, the CFA indicated that the items on the CBS-R are clearly distinguishable from the items on the psychological aggression (as measured with the subscales of the revised Conflict Tactic Scales [CTS2]), and that this holds for both males and females. Implications for the general use of the CBS-R and for use in conjunction with psychological aggression and physical aggression in intimate partner violence were discussed.